Het Langhuis 1983 - 1986. (Zwolle : Galerie Langhuis, 1987)
van Ark, Charl ; Bogaerts, Rene ; Dera, Cor ; Geerts, Peter ; Korten, Rene ; Kreiter, Anne ; Ludwig, Rudi ; van der Meijden, Theo ; Notermans, Victor ; Scholten, Nico ; Spruit, Carla ; Veugen, Helma
Overzicht tentoonstellingen en aktiviteiten van Galerie Langhuis Zwolle 1983-1986
Nederlands
boek